Agroecology and La Vía Campesina II. Peasant agroecology schools and the formation of a sociohistorical and political subject - Rosset, Peter Michael [UNESP]; Val, Valentín; Barbosa, Lia Pinheiro; Mccune, Nils (Universidade Federal do Paraná, 2021)
Scaling up of peasant agroecology and building food sovereignty require major transformations that only a self-aware, critical, collective political subject can achieve. The global peasant movement La Vía Campesina (LVC), in its expression in Latin America, the Coordinadora Latinoamericana de Organizaciones del Campo (CLOC), employs agroecology and political training or formation as a dispositive or device to facilitate the emergence of a sociohistorical and political subject: The agroecological peasantry, designed to be capable of transforming food systems across the globe. In this essay, we examine the pedagogical philosophies and practices used in the peasant agroecology schools and training processes of LVC and CLOC, and how they come together in territorial mediation as a dispositive for pedagogical-educational, agroecological reterritorialization.
Agroecología y La Vía Campesina II. Las escuelas campesinas de agroecología y la formación de un sujeto sociohistórico y politico
Keywords: Agroecology; CLOC; Education; La Vía Campesina; Political subject; Scaling